ACTITUDES Y PERCEPCIONES DE ESTUDIANTES DE ODONTOLOGÍA POSTERIOR A LA APLICACIÓN DE UN VIDEO Y PODCAST EN LÍNEA FRENTE A UNA ESTRATEGIA EDUCATIVA TRADICIONAL EN EL CURSO DE ENDODONCIA. UN ESTUDIO DE CORTE TRANSVERSAL - García-Rupaya, Carmen Rosa (2025)
Objective: To evaluate the attitudes and perceptions of dental students following the implementation of an online video and podcast compared to a traditional educational strategy in the Endodontics course. Materials and Methods: This descriptive cross-sectional study was conducted among students enrolled in the Endodontics course. A measurement instrument was developed and validated through expert judgment; it consisted of fifteen items assessing attitudes and ten questions regarding perceptions. A 4.30-minute video was created on the topic of chamber access in maxillary teeth, and a 15-minute podcast was produced on pulpal lesions. Gender-based comparisons were conducted using the Wilcoxon test. Additionally, Chi-square and Fisher's exact tests were applied for individual item associations with the gender covariate. A significance level of α < 0.05 was adopted. Results: A total of 21 male students (38%) and 34 female students (62%) participated, with a mean age of 22.80 years. The average attitude score was 67.33, with a maximum of 75 and a minimum of 55 points. A statistically significant difference was found between the scores of male and female students (p = 0.025). An association was observed between attitudes toward the use of the video (p = 0.049) and the podcast (p = 0.041) and the student’s gender. Additionally, 67.27% of students perceived that all three educational strategies should be used in the teaching process of endodontics. Students identified strengths in both the video and podcast, with no reported weaknesses. Conclusion: The use of video and podcast in endodontics may serve as a valuable alternative to complement the content provided in undergraduate dental education.